How the Lion Lost his Lunch - "Wilson, David" (Macmillan Children's: London, 1996)
Jeremy James finds some strange inhabitants in Warkin-on-Sea: a lion, a non-go, non-stop donkey, a lady who hates children, and monkeys who eat cars.
Keywords: Children's stories-English Fiction